The Foreign News and Media Image of the European Union in Current Television News Production - Greguš, Ľuboš; Kačincová Predmerská, Anna (Communication Today, 2020)
The aim of the presented theoretical-empirical study is to find quantifiable data reflecting information about foreign societies in foreign news through a case study, in which we use quantitative content analysis, focusing on the occurrence of information about events in the European Union and their thematic context. We point out the thematic connection and the position of the European Union in broadcasting in comparison with information about individual states of the world and mainly European countries. Due to the broad spectrum of the topic, we opted for a case study on the Slovak news television TA3, while the research material represented all news content focused on foreign events broadcast during a period of two months (1,621 news items). The theoretical part of the study is focused on a brief definition of key terms, in this case news, agenda setting, pro-Europeanism and Euroscepticism. The results of the research point to the dominant position of the European Union in the broadcasting of the chosen television news, while this international grouping of states is presented as a unified political entity appearing in international political events as an entity equivalent to other countries.